PENELAAHAN PENGARUH WAKTU PENGKONDISIAN DAN PENGGUNAAN PARAFIN PADA CONTOH UJI TERHADAP EMISI FORMALDEHIDA PAPAN PARTIKEL - Adi Santoso; Paribotro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 2002)
Determination of the formaldehyde emission from particleboard can correspond to the American and Japan Standards. However, the difference in preparing the test sample of particlebourd can bring about different results on the determination of such formaldehyde emission. this report deals with assessing the effect of conditioning duration and the use of paraffin in preparing the test sample of particleboard in accordance with both American and Japan Standars on the formaldehyde emission.The results revealed that conditioning duration and the me of puroffin affected significantly theemission of formaldehyde from the tested sample of particleboard the longer the duration, the lower, the emission level. Meanwhile, the use of paraffin on the particleboard sample tended to lower its formaldehyde emission than the one from the sample without paraffin. The relation between conditioning duration (X) and formaldehyde emission (Y) could further be expressed in linear regression equations with significant negative correlation coefficients (r) as follows: Without paraffinY = 4.20- 0.27X ( r = - 0. 9348); US standardY = 12.68- 0.98X ( r = - 0. 9433 ); Japan standard with paraffin.Y= 2.75 - 0.22X ( r = - 0.9756); US standardY = R.46 - 0.33X ( r = - 0.9824); Japan standard At a given conditioning duration, the average emission of formaldehyde from the particleboard with paraffin decreased by 1.61 µg/mm (according to American Standards) and 2.14 µg/ml (according to Japan Standard). Therefore, such figures confirmed the case that different sample preparation to particleboard in accordance with American and Japan Standards brought about different levels of formaldehyde emission.